Utilization of Radium 226 from the oncology center – evaluation of staff exposure - Andryskowski, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2007)
226 Ra found application in oncological therapy due to its long half-life and the type of emitted radiation. After many years of application it was replaced by less radiotoxic short-lived isotopes. In some oncology centres 226 Ra is still stored even though it is not used in therapy. The necessity of sealing it in glass, which is associated with long-lasting and direct exposure of a worker to radiation, is an indispensable condition if radium is to be collected by the Radioactive Waste Disposal Plant. The aim of the study is to present the problem of radium utilization on the basis of our own experience, which will make it easier to perform these activities in other oncology centers in Poland. After the initial analysis, it was calculated that a person working for 3 hours at a distance of 50 cm from 72 unprotected sources of radium 266 of total activity of 31 GBq would be exposed to a dose of 91.5 mSv. As this dose is about five times higher than the annual effective dose for category A workers, work in such conditions is strictly prohibited. After application of a lead shield, decrease of the dose (simultaneous exposure to the activity of only 5 sources) and the use of a hand-held gas burner enabling work behind the lead shield, a worker sealing radium in glass is exposed to a dose of 2 mSv. Estimation of the exposure was performed on the basis of individual and environmental dosimetry, measurement of radioactive contamination and dose rate. Mathematically calculated analysis of the hazard enabling determination of precise working conditions is a necessity which must be fulfilled before performing these activities. In the evaluation of hazard, not only external exposure was taken into account but also the possibility of external and internal exposure as well. Before starting work leakproofness of the sources was controlled.